Uang, Politik dan Kekuasaan: Adakah Peluang Bagi Etika Politik? - Haryatmoko Haryatmoko (Respons: Jurnal Etika Sosial, 2008)
The purpose of this exposition is to understand the quality of people participation as an indicator to measure the effectiveness of democracy. The article emphasizes strongly that effectiveness of democracy can be realized if democracy is oriented to solve the problem of injustice in society. People have real alternatives in both politics and economy in order to avoid being exploited and manipulated by political authorities and economic agents.